Enhanced sensitivity of caterpillar-like ZnO nanostructure towards amine vapor sensing. (October 2021) - Gupta, Santosh K.; Mohan, Swati; Valdez, Marisol; Lozano, Karen; Mao, Yuanbing
Abstract: Owing to the uprising health issues due to amine exposure, this work has been taken up to design a novel caterpillar-like ZnO nanoarchitecture using a combined hydrothermal and Forcespinning® technology for sensing amine vapor. This study presents two different approaches to investigate the sensing behavior of the caterpillar-like ZnO nanostructure compared to both commercially available ZnO nanoparticles and laboratory synthesized carbon/ZnO composite fibers. It is found that ZnO caterpillar-like nanostructure shows the best performance owing to its highest surface to volume ratio. Electrochemical investigations suggest maximum enhancement in current density from the caterpillar-like ZnO nanostructure on amine exposure due to the increased involvement of electron pair of nitrogen owing to its high hydroxyl concentration. Photoluminescence spectroscopy depicts defect induced blue emission owing to defect in native ZnO nanoparticles which quenches on amine exposure. The quenching has been found to be monotonic over the entire range of exposed n-propyl amine (NPA, 0–500 ppm) and attributed to defect annihilation upon exposing to amine vapor. Optical detection of NPA by the caterpillar-like ZnO nanostructure based on emission quenching shows a linear response in the studied NPA concentration range with a detection limit (LOD) of 12.54 ppm. Our results demonstrate the importance of structure, morphology and architecture of ZnO for gas sensing activity. Highlights: Novel caterpillar-like ZnO nanostructure (CZN) was designed. Sensing behavior of CZN was compared to commercial ZnO NPs and C/ZnO composite fibers. Enhancement in current density of the caterpillar-like ZnO nanostructure on amine exposure. Quenching of defect induced blue emission on amine exposure. Linear response towards amine vapor in the range 0–500 ppm with detection limit of 12.5 ppm. Graphical abstract: This work demonstrated enhanced sensitivity of caterpillar zinc nanostructure towards amine sensitivity Image, graphical abstract